Successful Grafting of Two Indonesian Clones of Piper nigrum L. with P. colubrinum Link.: Effects of IBA and NAA on Rooting and Effects of BA on Grafting - Yusnita, Yusnita; Hapsoro, Dwi; Prayogi, Adi Noor; Agustiansyah, Agustiansyah; Karyanto, Agus (AGRIVITA Journal of Agricultural Science, 2024)
This study aimed to investigate the effects of auxin types and their concentrations on rooting of the rootstock cuttings and BA on grafting. First, IBA, NAA or IBA+NAA, each at 0, 1000, 2000, and 3000 ppm were used as treatments to study rooting of Piper colubrinum. In the second experiment, BA (0 and 50 ppm) was applied to P. nigrum scion clones of Natar-1 and Petaling-2, before being grafted to the rootstocks. Results showed, that all types of auxins (IBA, NAA or IBA+NAA) induced rooting and shoot growth, and the increase of auxin concentrations led to the increase of rooting. However, their effectiveness was different. NAA and IBA+NAA were superior to IBA, and at 2000 ppm, IBA+NAA resulted in the best plant growth, as indicated by higher values of both rooting and shoot growth parameters. Compared to control, BA treatment on scions resulted in higher grafting success (80% vs. 93%) for Natar-1, and (73% vs.100%) for Petaling-2 clones.  BA treatment on scions also induced more calluses in the graft union and better shoot growth. To our knowledge, this is the first report on the use of BA to increase success of grafting between P. nigrum and P. colubrinum.